1984
DOI: 10.1002/app.1984.070290504
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of dyes onto chitin in fixed bed columns and batch adsorbers

Abstract: SynopsisChitin has the ability to adsorb substantial quantities of dyestuffs from aqueous solutions. Consequently, it may be a useful adsorbent for effluent treatment from textile mills. The design procedures for batch and continuous fixed bed adsorption columns have been investigated for four dyestuffs, namely, CI Acid Blue 25 (Telon Blue ANL, Bayer), CI Acid Blue 158 (Neolan Blue 29, Ciba Geigy) CI Mordant Yellow 5 (Eriochrome Flavine A, Ciba Geigy), and CI Dirert Red 84 (Solophenyl Brown 3RL, Ciba Geigy). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 5 publications
1
56
0
Order By: Relevance
“…Langmuir, Freundlich, Temkin, Halsey and HarkinsJura isotherm equations). In order to understand the mechanism of MB adsorption on clay, the experimental data were fitted to the aforementioned equilibrium isotherm equations and the different isotherm parameters, obtained from the different plots, are presented in Table 1 2 were obtained when the experimental data were fitted into Freundlich and Halsey isotherm equations (0.999) for modified clay while unmodified clay are 0.971 and 0.987. The description of the sorption of MB on clay by the Freundlich isotherm equations is a pointer to the heterogeneity of the surface with a non-uniform distribution of heat of adsorption over the surface of the clay, while the Halsey isotherm fitting is an indication of the heteroporosity of the surface and the multilayer adsorption nature of the MB on clay.…”
Section: Equilibrium Isotherm Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Langmuir, Freundlich, Temkin, Halsey and HarkinsJura isotherm equations). In order to understand the mechanism of MB adsorption on clay, the experimental data were fitted to the aforementioned equilibrium isotherm equations and the different isotherm parameters, obtained from the different plots, are presented in Table 1 2 were obtained when the experimental data were fitted into Freundlich and Halsey isotherm equations (0.999) for modified clay while unmodified clay are 0.971 and 0.987. The description of the sorption of MB on clay by the Freundlich isotherm equations is a pointer to the heterogeneity of the surface with a non-uniform distribution of heat of adsorption over the surface of the clay, while the Halsey isotherm fitting is an indication of the heteroporosity of the surface and the multilayer adsorption nature of the MB on clay.…”
Section: Equilibrium Isotherm Studiesmentioning
confidence: 99%
“…It has also been reported that many dyes and pigments have toxic as well as carcinogenic, mutagenic, and tetratogenic effects on aquatic life as well as humans [2,3]. The removal of dyes and organics in an economic fashion remains an important problem, although a number of successive systems have been developed with the adsorption technique [4].…”
Section: Introductionmentioning
confidence: 99%
“…The R L value implies the adsorption to be unfavourable for R L > 1, linear for R L = 1, favourable for the range 0 < R L < 1 or irreversible for R L = 0 [34].…”
Section: Linear Form Of Langmuir Equation Is Expressed Asmentioning
confidence: 99%
“…The isotherm constants were calculated from the linear form of each model and max and values for Langmuir isotherm, and 1/ values for Freundlich isotherm, and 2 values for both isotherms are given in Table 4. As can be seen from 2 values given in Table 4 The characteristics of the Langmuir isotherm could be expressed by a separation factor, , which is defined as [35] …”
Section: The Effect Of Ph Initial Dye Concentration and Contactmentioning
confidence: 99%